1997
DOI: 10.1111/j.1365-2621.1997.tb04426.x
|View full text |Cite
|
Sign up to set email alerts
|

Carrageenan Effects on Thermal Stability of Meat Proteins

Abstract: Meat myofibrillar protein (MP) gels and ground pork were used as model systems for studying thermal transition temperatures. Addition of up to 2% of , , or carrageenan (CGN) to MP caused a very slight change in the thermal denaturation of the meat proteins. Three transition temperatures were found in ground pork samples, which were characteristic of myosin (59.4ЊC), sarcoplasmic proteins (67.8ЊC), and actin (82.4ЊC). Mixtures of high ionic strength had lower thermal transition peaks. CGN did not cause major sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
3
7
0
Order By: Relevance
“…These proteins were reported to denature in the temperature range of 59-82°C. In the present study, the denaturation temperature was mostly between 71 and 83°C and hence the proteins are probably sarcoplasmic and actin as they match the literature value more closely than any other beef proteins (Barbut & Findlay, 1991;Bircan & Barringer, 2002;DeFreitas et al, 1997). The rheograms of beef puree showed similar patterns up to 65°C and only the one at 80°C showed a significant increase rather than conventional decreases.…”
Section: Beefsupporting
confidence: 81%
See 2 more Smart Citations
“…These proteins were reported to denature in the temperature range of 59-82°C. In the present study, the denaturation temperature was mostly between 71 and 83°C and hence the proteins are probably sarcoplasmic and actin as they match the literature value more closely than any other beef proteins (Barbut & Findlay, 1991;Bircan & Barringer, 2002;DeFreitas et al, 1997). The rheograms of beef puree showed similar patterns up to 65°C and only the one at 80°C showed a significant increase rather than conventional decreases.…”
Section: Beefsupporting
confidence: 81%
“…Reference to literature data on protein denaturation indicates that myosin, collagen and actin to be the principal protein components in lamb meat based baby foods. These proteins have been shown to have denaturation temperatures in the range of 54-60°C, 63-69°C and 71-83°C, respectively (Bircan & Barringer, 2002;DeFreitas et al, 1997;Murphy et al, 1998). The close proximity of current values to some of these is indicative of the presence of similar proteins in the system.…”
Section: Chickenmentioning
confidence: 91%
See 1 more Smart Citation
“…The thermal properties of these proteins are affected by pH and salt conditions (DeFreitas, Sebranek, Olson, & Carr, 1997a, 1997bEnsor, Sofos, & Schmidt, 1991;Quinn, Raymond, & Harwalker, 1980;Shiga, Kami, & Fuji, 1988;Stabursvik, Fretheim, & Froystein, 1984). The thermal denaturation changes of meat proteins that occur upon addition of nonmeat ingredients may indicate shifts in the physical state or interaction between meat proteins and nonmeat ingredient (DeFreitas et al, 1997a;Donatus & Xiong, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…In the second study, CGN was added to meat chunks rather than comminuted meat, resulting in fewer interactions. DeFreitas et al [113] added CGN to protein extracts from pork muscle and found no major shift in transitions. Salt is also a common ingredient in these products which destabilizes proteins.…”
Section: Rheology and Product Qualitymentioning
confidence: 97%